Water-Stable Pillared Three-Dimensional Zn–V Bimetal–Organic Framework for Promoted Electrocatalytic Urea Oxidation - Abazari, Reza; Sanati, Soheila; Stelmachowski, Pawel; Wang, Qiyou; Krawczuk, Anna; Goscianska, Joanna; Liu, Min (Inorganic chemistry, 2024)
Urea oxidation reaction (UOR) is one of the potential routes in which urea-rich wastewater is used as a source of energy for hydrogen production. Metal–organic frameworks (MOFs) have promising applications in electrocatalytic processes, although there are still challenges in identifying the MOFs’ molecular regulation and obtaining practical catalytic systems. The current study sought to synthesize [Zn6(IDC)4(OH)2(Hprz)2] n (Zn-MOF) with three symmetrically independent Zn(II) cations connected via linear N-donor piperazine (Hprz), rigid planar imidazole-4,5-dicarboxylate (IDC3–), and −OH ligands, revealing the 3,4T1 topology. The optimized noble-metal-free Zn0.33V0.66-MOF/NF electrocatalysts show higher robustness and performance compared to those of the parent Zn monometallic MOF/NF electrode and other bimetallic MOFs with different Zn–V molar ratios. The low potential of 1.42 V (vs RHE) at 50 mA cm–2 in 1.0 M KOH with 0.33 M urea required by the developed Zn0.33V0.66-MOF electrode makes its application in the UOR more feasible. The availability of more exposed active sites, ion diffusion path, and higher conductivity result from the distinctive configuration of the synthesized electrocatalyst, which is highly stable and capable of synergistic effects, consequently enhancing the desired reaction. The current research contributes to introducing a practical, cost-effective, and sustainable solution to decompose urea-rich wastewater and produce hydrogen.